The discourse of indigenism in Manuel González Prada and Luis E. Valcárcel - Gonzales Alvarado, Osmar (2008)
EThis article presents a comparative perspective of indigenist discourses in two Peruvian thinkers who had a great influence on the Peruvian cultural environment at the end of the 19th century and the beginning of the 20th: Manuel Manuel González Prada and Luis E. Valcárcel. The first is representative of an indigenism from an anarchist perspective and the second represents an indigenism of a Marxist nature. Both visions are important to understand the phenomenon of indigenism in Peru.